Six Sigma: The Panacea to Sustainability - Krambia-Kapardis, Maria; Ioannou, Adrian (My University, 2011)
Whilst there are a number of qualified methodologies, the researchers have opted to utilise the tools available through Six Sigma to prove that Six Sigma can be used to save resources and improve quality and process. Five industry sectors were identified as the ones to be surveyed using quantitative and qualitative methods and finally piloting the results on five different SMEs. Since this is a relative new methodology to the Cypriot entrepreneur and regrettably at the time of carrying out the study an international financial crisis caused a lot of financial problems to many respondents and as such could not see the immediate effects or benefits of Six Sigma and were reluctant to co-operate or participate. The Six Sigma methodology can be customized to industrial sectors and a tailored version of the methodology can be developed for a particular process or problem. The paper illustrates the problem areas identified from both the qualitative and quantitative research per industry. This is the first study carried out on Six Sigma in a small economy like Cyprus and tested on five industry sectors using both qualitative and quantitative method
Keywords: Six Sigma; Sigma; Lean; DMAIC; ISO 9000; EFQM; TQM; SME; CAF; Industry sectors; Cyprus